STUDENTS WORKSHEET BASED ON 7E LEARNING CYCLE: STRATEGIES TO IMPROVE ACTIVITIES AND UNDERSTANDING THE CONCEPT OF EXCRETION SYSTEM IN MA - Rukmana, Avita; Alimah, Siti (Journal of Biology Education, 2019)
This study aims to determine the effect of students worksheets of 7E learning cycle on activities and understanding the concept of excretion systems at MAN 1 Jepara. The research method used was pre-experimental design with one shot case study. Population of this research was all the students of XI class at MAN 1 Jepara with the samples were XI MIPA 2 and XI MIPA 3 which were taken by purposive sampling. Research data in the form of student activities taken with an observation sheet and understanding the concepts taken with a test. Student activity data were analyzed descriptively quantitatively while understanding the concepts was analyzed by Wilcoxon and N-gain. The results of the study show that the average activity value of XI MIPA 2 students is 88.99% and XI MIPA 3 is 88.63% with the criteria of both classes were very high. The average results of conceptual understanding of students of class XI MIPA 2 is 78.67 with classical completeness is 87.18% while class XI MIPA 3 is 81.73 with classical completeness of  91.89%. The results of the analysis using the Wilcoxon show that the sig value. 0,000<0,05, means that there are significant differences between the results of the pretest before the application of student worksheet based on 7E learning cycle and posttest results after the application of student worksheet based on 7E learning cycle. The results of the N-gain test showed an increase in understanding of concepts in class XI MIPA 2 and XI MIPA 3 of 0.565 and 0.588 with medium criteria. Based on the results of the study it can be concluded that learning using the students worksheet based on 7E learning cycle influences the activity and understanding of the excretion system concept of the XI grade students of MAN 1 Jepara.